The Effect of Intradermal Botulinum Toxin a injections on painful diabetic polyneuropathy. Issue 6 (November 2020) - Taheri, Mehrdad; Sedaghat, Meghdad; Solhpour, Ali; Rostami, Pooya; Safarpour Lima, Behnam
Abstract: Background and aims: Botulinum toxin type A (BTX-A) have been recently administered to improve Diabetic neuropathies; however, the efficacy of this treatment for relieving pain in painful diabetic polyneuropathy (DPN) has not been studied yet. Herein, we investigated the efficacy of botulinum toxin A (BTX-A) on DPN. Methods: This prospective, randomized, double-blind, controlled trial was performed in Imam Hossein Medical Center, pain clinic (Tehran, Iran). Diabetic patients (141 cases), between 40 and 70 years old with polyneuropathy in lower limbs were randomly assigned to one of these three groups: 1. Group D1 received 150 units of BTX-A in one foot and normal saline 0.9% in the other foot, 2. Group D2 received BTX-A 150 units in both feet, 3. Group N received normal saline 0.9% in both feet. All injections were performed intradermally using insulin syringes in 20 different points of foot. Visual analogue scale (VAS) and neuropathy pain scale (NPS) were used to compare the groups. Results: The improvement of VAS, pain intensity, sharp and hot sensation, sensitive and unpleasant sensation, deep and surface sensation was significant when comparing BTX-A and placebo groups. However, dull and cold sensations improvement (p = 0.114, and p = 0.653; respectively) did not show a significant difference between BTX-A injection and placebo groups. Furthermore, the percentage of changes after treatment indicated that sharp pain was improved more than other complaints (80%, 81%, and 37% for D1, D2, and N groups; respectively). Conclusion: Intradermal administration of BTX-A was effective in improving VAS and all of the items of NPS in patients with diabetic polyneuropathy, except for dull and cold sensation. Highlights: Intradermal administration of Botulinum Toxin A (BTX-A) on the foot seems to improve diabetic polyneuropathy. Diabetic patients who received unilateral BTX-A injections showed improvement in both feet. BTX-A injection exerted its effect mostly on the improvement of sharp pain sensation.